An essay on the crisis of capitalism: A la Marx? - Korkut Ertürk (The University of Utah, Department of Economics, 2012)
The essay argues that a crisis of collective agency is at the root of the global economic crisis we face today. The secret of prosperous capitalism, the so-called golden age, was the ability of the state to uniformly impose welfare enhancing market restrictions that made it possible to husband and invest in common pool resources. This ability has waned during the neoliberal era and the result has been a resurgence of forces of competition, what Marx called the law of value, generating long term collective costs that go increasingly unaddressed. This is reminiscent of classical capitalism's main weakness with respect to organizing corrective collective action, making a couple of Marx's point resonate today. One is his view of competition as a war like process and how that militates against coordination (not to mention cooperation) among individual capitalists. The second point is the very basis of Marx's main gripe with capitalism: the two different ways for accounting for economic performance, one, based on profits and the other on human welfare can become deeply divergent. The failure of collective agency ties together the two points. What is profitable at the micro level ends up being at variance with human welfare as well as the long term collective interest of capitalists, because coordination failure is not only endemic but a defining characteristic of capitalist competition.
Keywords: P16; O16; D70; 330; collective action club goods; welfare state; financial crisis; Marx